Body composition, somatotype, and physical fitness of mixed martial arts athletes - Marinho B.F. (2016)
© 2016, Springer-Verlag Italia.Purpose: To describe the morphofunctional characteristics of elite mixed martial arts athletes. Methods: Eight male Brazilian athletes (aged: 31 ± 5 years; training experience: 5 ± 1 years; height: 1.77 ± 0.05 m; body mass: 82.1 ± 9.6 kg) with national training experience were subjected to anthropometric evaluation to estimate body composition and somatotype, and maximal strength (1 RM) in squat and bench press, abdominal and upper limb endurance, and lower limb power were determined. Results: Body fat levels of 13.4 ± 5.6 %, lean mass levels of 69.6 ± 4.6 %, and mesomorphic component (6.4 ± 0.8) were observed. Athletes performed 42 ± 14 sit-ups and 37 ± 9 push-ups, and remained for 35 ± 10 s in the flexed-arm hang test. Athletes reached 2.19 ± 0.31 m in the horizontal jump test, and obtained absolute 1-RM values of 80 ± 15 kg and 68.5 ± 6.0 kg and relative values of 1.00 ± 0.2 kg/kg and 0.84 ± 0.10 kg/kg in bench press and squat tests, respectively. Conclusion: Results indicate body fat levels in accordance with other studies, high lean body mass, and a predominantly mesomorphic component. Abdominal and upper limb endurance were classified as excellent, while results of the flexed-arm hang test were similar to previous data. Mixed martial arts athletes’ lower limb performance in the horizontal jump was classified as weak. Lower levels of maximal strength were obtained in squat and bench press tests.